2021
DOI: 10.1007/s11661-021-06480-6
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Bainitic Steel for Rail Applications Based on Carbide-Free, Low-Alloy Steel

Abstract: This paper describes the development and characterisation of bainitic steel for rail applications based on carbide-free, low-alloy steel. The results show that after rolling and subsequently cooling, the designed carbide-free bainitic steel exhibits better mechanical performance than standard pearlitic steel. This is because of its fine, carbide-free bainitic microstructure, which consists of bainitic ferrite and retained austenite laths. Microstructural and mechanical property analysis was carried out using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 95 publications
1
5
0
1
Order By: Relevance
“…It was determined that in the crack area the dislocation density of bainitic ferrite decreased compared to the base material (Table V). A similar result was also found in the research on cyclic deformation, [12] therefore also in the case of the area crack tip/matrix interaction, the change in dislocation density may be caused by the formation of sub-grains. Also, it is another observation supporting this hypothesis along with the size of the crystallites.…”
Section: The Microstructure Evolution Prior the Crack Tipsupporting
confidence: 85%
See 2 more Smart Citations
“…It was determined that in the crack area the dislocation density of bainitic ferrite decreased compared to the base material (Table V). A similar result was also found in the research on cyclic deformation, [12] therefore also in the case of the area crack tip/matrix interaction, the change in dislocation density may be caused by the formation of sub-grains. Also, it is another observation supporting this hypothesis along with the size of the crystallites.…”
Section: The Microstructure Evolution Prior the Crack Tipsupporting
confidence: 85%
“…It was found that the dislocation density decreased at the crack tip, which was supported by the formation of sub-grains. [12] Due to the technological properties and the prospects for industrialization, [70] bainitic steels subjected to continuous cooling are vastly promising. The variety of bainite morphology and different proportions of phases after continuous cooling directly influence the mechanisms of their fracture.…”
Section: E Discussion-the Crack Path Evolution and Influence Of Crack...mentioning
confidence: 99%
See 1 more Smart Citation
“…As far as steels are concerned, recent papers on complex phase [6], multiphase [7], ferritic/martensitic [8], pipeline [9], and bainitic steels [10] should be mentioned. Modern bainitic steels are used for manufacturing rails [11] and rods [12]; the latter mainly has further application as stock for cold heading processes [13].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the cooling rate of steels, the ferrite (F), pearlite (P), bainite (B), or martensite (M) microstructures could be formed due to the displacive and reconstructive transformations of austenite (A) crystal structure, which are accompanied with cementite precipitation at different diffusion rates [1]. It is well known that the volume fraction, dimension, and morphology of these microstructure phases are greatly responsible for the mechanical properties of steels [2]. In this case, the correct classification of these microstructure features is crucial during the metallographic investigation to understand their role in material performance.…”
Section: Introductionmentioning
confidence: 99%